U.S. Copyright Renewals, 1963 January - June - Library of Congress. Copyright Office (Salt Lake City, UT : Project Gutenberg, 2004)
"U.S. Copyright Renewals, 1963 January - June" is a reference guide detailing renewal registrations for various literary works, including books, pamphlets, serials, and contributions to periodicals, created during the early 1960s. The text appears to be organized systematically with entries listed alphabetically by author or title, providing a comprehensive resource for copyright claims made during this specific time frame. The opening of this publication introduces a systematic list and explanations about the registration process for copyrights, highlighting how registered materials are organized. Each entry typically includes specific details like the title, authors, and relevant dates regarding the original and renewal registrations. This initial portion of the resource effectively establishes its purpose and acting as a chronological archive that may be beneficial for researchers, publishers, and authors looking to understand the landscape of copyright during that period. (This is an automatically generated summary.)
Release date is 2004-03-01
Produced by Michael Dyck, Charles Franks, pourlean, and the Online Distributed Proofreading team, using page images supplied by the Universal Library Project at Carnegie Mellon University
Keywords: Copyright -- United States -- Catalogs